2015
DOI: 10.1111/cobi.12561
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of China's National Forest Protection Program and nature reserves

Abstract: There is profound interest in knowing the degree to which China's institutions are capable of protecting its natural forests and biodiversity in the face of economic and political change. China's 2 most important forest-protection policies are its National Forest Protection Program (NFPP) and its nationallevel nature reserves (NNRs

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 35 publications
0
105
0
3
Order By: Relevance
“…Additionally, the results of this study suggest that an increase in the area of nature reserves should decrease the rate of bird species decline. Currently, the area of nature reserves (7.4% of the land area) on Hainan is small compared to the area of reserves (14.9% of the land area) throughout China (Ren et al, 2015). Thus, designating more natural forest areas for nature reserves may be an effective approach for conserving bird diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the results of this study suggest that an increase in the area of nature reserves should decrease the rate of bird species decline. Currently, the area of nature reserves (7.4% of the land area) on Hainan is small compared to the area of reserves (14.9% of the land area) throughout China (Ren et al, 2015). Thus, designating more natural forest areas for nature reserves may be an effective approach for conserving bird diversity.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has advantages-e.g., it may strengthen ties with local communities and other stakeholders who benefit from parks, and provides incentives for park managers to show and communicate the value of parks-but it has disadvantages as well. Park functions or entire parks that are important but less popular with the public may be underfunded (NPS, 2011;Ren et al, 2015), and management decisions may be influenced by private interests unrelated or counterproductive to achieving the mission of the National Park Service. Moreover, the volume of private philanthropy and other non-government funding opportunities is not adequate to make up for the shortfall in government investment (Vaughn and Cortner, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Surveys across 1000 protected areas of all types, not just national nature reserves, found that 25% have annual revenues above US$771,000 (5 million CNY), whereas 38% operate on less than US$77,000 (500,000 CNY) and 11% on less than US$7700 (50,000 CNY) (Zhong et al, 2015). Because of this underfunding, illegal hunting, logging, water pollution, and illegal wildlife trade are problems in some reserves (roughly 6-15%, based on surveys) limiting their ability to protect resources (Zhong et al, 2015), although recent analyses suggest that reforestation efforts within protected areas have been successful at the national scale (Ren et al, 2015).…”
Section: Substantial Government Investmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Key words: Shennongjia National Nature Reserve; carbon sequestration; conservation effectiveness; forest ecosystem; carbon pool 建立自然保护区是维持生物多样性和生态系 统功能稳定的最有效方式 (Joppa et al, 2008;Pouzols et al, 2014) (Andam et al, 2008;Wu et al, 2011;Hill et al, 2015;Ren et al, 2015), 目前, 有关保护区保护成效 的研究大多集中于生物多样性保护方面 (Bruner et al, 2001;Rodrigues et al, 2004;Cao et al, 2015;Jenkins et al, 2015;Chen et al, 2017 (Tans et al, 1990;Dixon et al, 1994)。森林碳储量即便小幅度的 变动, 也可能影响整个大气CO 2 的浓度, 进而对陆 地生态系统的分布、组成、结构和功能产生影响 (Schimel et al, 2000)。 保护森林的固碳能力已成为自 然保护区的一项重要功能之一。 关于保护区保护森林固碳的成效, 目前仅开展 了少量研究 (Gaston et al, 2008;Willcock et al, 2016;Bowker et al, 2017;Scherer et al, 2017) 1990-2010 (1990-2000; 2000-2010) 0 …”
unclassified